Europe in emerging Asia opportunities and obstacles in political and economic encounters - Erixon, Fredrik; Srinivasan, Krishnan 1937- (Rowman & Littlefield International, 2015)
This book explores the relationship between European and emerging Asian economies, as globalization changes the international economic and political landscape. Reflecting on past interactions and possibilities for the future, the book brings together Asian and European perspectives from former politicians, diplomats, and academic experts to examine questions around trade and security, rights and climate change, identity clashes, and the colonial legacy. The book is a timely consideration of highly topical questions that will shape international politics in the twenty-first century.